Analisis Variasi Suhu Pencampuran Terhadap Durabilitas Asphaltic Concrete-Wearing Course (AC-WC ASB H) - Ramlan, Ratnasari; Hanusu, Abdi; Setiawan, Arief (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2015)
Asbuton is a natural asphalt found in Buton Island, South-East Sulawesi with preservation approximately 210 million tonnes particularly found in Lawele area. Warm Mixing Asbuton usually uses temperature of 120°C - 125°C in Special Specification Warm Mixing of Asbuton. In mixing, temperature is one of the most important factors in the construction of road work and it also influences the characteristics of the mixture that are the durability and rut resistance. This study aims to understand the influence of temperature variation of Asbuton warm mixing against ACWC mixing durability and the best durability of some mixing temperature variations. The temperature variation used in mixing and compaction are 105ºC and 95ºC, 115ºC and 105ºC, 125ºC and 115ºC. This study were using Asbuton Butir T 15/25 Ex. Bina Prima Indonesia (BPI), with fluxing materials, which is mixtures from asphalt penetration 60.70 and solar Ex.Pertamina with materials taken from Stone Crusher Ex.Taipa River. The research were  utilyzes Marshall Test to obtain  the characteristic of mixing, referring to SNI and Bina Marga. The result showed that durability is highly influenced by temperature variation of mixing and compacting. Mixing temperature of 105°C and compaction of 95°C are not recommended because the mixing durability does not meet  the specification. On the other hand the highest temperature is resulting in mixing durability that still meet the good specifications.